العدالة الدستورية في توزيع الوظيفة التشريعية في النظام الدستوري الجزائري والتونسي - غانس, حبيب الرحمان (جامعة الوادي University of Eloued, 2019)
ملخص: إن التحول الذي أحدثه دستور الجمهورية الفرنسية الخامسة أدى إلى قلب العديد من المفاهيم الدستورية التقليدية، ومن بينها تلك القاعدة التي كانت تجعل الوظيفة التشريعية حكرا على البرلمان، فنجد العديد من الدساتير قد تأثرت بالدستور الفرنسي ومنها على وجه الخصوص الدستورين الجزائري والتونسي، الأمر الذي أدى إلى تقليص مجال تدخل البرلمان سواء على مستوى الوظيفة الرقابية أو على مستوى ممارسة الوظيفة التشريعية في مقابل تقوية السلطة التنفيذية، حيث قامت كل من الجزائر وتونس بتبني ما يسمى بعقلنة العمل البرلماني، غير أن النصوص الدستورية والممارسة العملية سارت على النهج الذي يعتمد على تقليص مجال تدخل البرلمان في ميدان التشريع مقابل توسيع نطاق تدخل السلطة التنفيذية، وبالذات في مجال سن القواعد القانونية حتى غدت تمارس الجزء الأهم من الوظيفة التشريعية ولم يعد التنفيذ سوى جزء من المهام التقليدية التي تقوم بها، وترتب على ذلك كله أن السلطة التشريعية لم تعد المشرع الوحيد أي أنها لم تعد هي صاحبة الاختصاص الواسع والأصيل في المجال التشريعي، بل إن دورها اقتصر في معظم الأحيان على التداول حول ما تقدمه إليها السلطة التنفيذية فترفض أو تقبل أو تعدل و لكنها قلَما تبادر. abstract The Transformation of many traditional constitutional concept is a major result which is caused by the chance of the constitutional of the 5 French republic - this latter affect many constitution especially the Algerian and the Tunisian, at the level of both the two functions supervisory or legislative function in Exchange for the reinforcement and the strengthening of the executive power . Rationalization of parliamentary work was adapted by Algeria and Tunisia. They set and establish a very important step on reducing the scope of parliamentary intervention of the executive it is obvious and clear in the area of instrument of legal norms which is a basis pass of the legislative functions, among the traditional functions we have only implementation nowadays the legislative authority is not the sole of legislator and it isn't accompanied by brood or original jurisdiction in the legislative field but not in its role and interest , that usually depends on the deliberation approximately the offer, the rejection, the acceptance or the modification but seldom be the first or initiative.
Keywords: السلطة التنفيذية، رئيس الجمهورية، البرلمان، رئيس الحكومة، مجلس نواب الشعب، التشريع بأوامر، المراسيم; Executive Authority. President of the Republic. Parliament. Head of Government. House of Peoples Representative. Legislation of Orders. Decrees.